Small Structural Differences between Two Ferrocenyl Diphenols Determine Large Discrepancies of Reactivity and Biological Effects. (24th September 2019) - Tonolo, Federica; Salmain, Michèle; Scalcon, Valeria; Top, Siden; Pigeon, Pascal; Folda, Alessandra; Caron, Benoit; McGlinchey, Michael J.; Toillon, Robert‐Alain; Bindoli, Alberto; Jaouen, Gérard; Vessières, Anne; et al.
Abstract: The ferrocenyl diphenol complexes 1, 1‐bis(4′‐hydroxyphenyl)‐2‐ferrocenyl‐but‐1‐ene (1 ) and 1, 2‐bis(4′‐hydroxyphenyl)‐1‐ferrocenyl‐but‐1‐ene [( Z )‐2 ], which differ by the relative position of the two phenolic substituents, display dramatically different antiproliferative activities on cancer cells (1 is far more cytotoxic than2 ). In this study, our goal was to discover the origin of this difference by comparing their reactivity and biological behaviour. In terms of common behaviour, we found that1 and2 are both efficient inhibitors of thioredoxin reductase (TrxR) in vitro after oxidation by a horseradish peroxidase/H2 O2 system. However, as1 is only a moderate inhibitor of TrxR in MDA‐MB‐231 cells, TrxR is probably not the major target responsible for the cytotoxicity of1 . In terms of differences, we noted that1 induced a significant redox imbalance characterised by lipid peroxidation and thiol oxidation, and a moderate decrease of the mitochondrial membrane potential in breast cancer cells, whereas2 has almost no effect. These results underline the importance of the trans configuration in the ferrocenyl–double bond–phenol motif, which is present in1 but is cis in ( Z )‐2 . Abstract : The trans configuration in the ferrocenyl–double bond–phenol motif drives anticancer activity: Complex1 is highly cytotoxic to breast cancer cells and induces a redox imbalance, whereas2 shows only modest cytotoxicity. This difference can be rationalized by the fact that only1 has the " trans " configuration responsible for its unique redox properties and strong anticancer activity.